Irobot Create mobile platform teleoperation (MASKAY, 2013)
The research topic is focused on the Teleoperation of the Irobot Create mobile platform, which iRobot Corporation distributes. Teleoperation consists of sending commands to said platform to execute movements, using a PC-based HMI, and the teleoperation interface is also capable of showing images of the environment of the mobile platform with the help of a mounted analog camera.
Keywords: teleoperation; iRobot; Wi-Fi